Evaluating the clinical efficacy of Du Huo Ji Sheng Tang in conjunction with electroacupuncture, hydroacupuncture, acupressure massage in patients with lumbosacral radicular syndrome caused by lumbar spine degeneration (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the clinical outcomes of the Du Huo Ji Sheng Tang herbal formula combined with acupuncture, electroacupuncture, and massage techniques using acupressure in case of lumbosacral syndrome resulting from spinal degeneration.Methods: In this study, inpatients at Can Tho City Traditional Medicine Hospital, diagnosed with lumbosacral syndrome related to lumbar spinal degeneration, were selected as subjects of a clinical intervention study without a control group, consisted of 32 cases treated with a combination therapy of Du Huo Ji Sheng Tang herbal formula along with electroacupuncture, hydroacupuncture, and acupressure massage, lasting for 14 days. Assessment of indicators was conducted at three time points: baseline, 7-day post-treatment, and 14-day post-intervention evaluations.Results: At the 14-day post-intervention mark, the pain intensity index (VAS) showed a notable attenuation, falling from 6.94 ± 0.72 to 2.47 ± 0.84 (p < 0.001). Schober scores, Lasègue test, and patients' ability to perform daily activities, as determined by the ODI scale, all showed significant improvement (p
Keywords: Lumbosacral syndrome, Du Huo Ji Sheng Tang, hydroacupuncture, electroacupuncture, massage combined with acupressure.